2004
DOI: 10.1021/jf030685x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Seasonal Variation of the Essential Oils from Two Mandarin Cultivars of Southern Brazil

Abstract: Cold-pressing and hydrodistilled peel oils of two Brazilian mandarin cultivars, commonly called Cai and Montenegrina (Citrus deliciosa Tenore), were obtained from fruits collected on mandarin trees submitted to the same pedoclimatic and cultural conditions. Their chemical composition and seasonal variation of the main volatile constituents were investigated by capillary GC and GC-MS, and the results were submitted to statistical analysis. To better characterize the oils, the enantiomeric distribution ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 11 publications
(17 reference statements)
3
25
1
1
Order By: Relevance
“…c P-value: *P # 0.05; **P # 0.01; ***P # 0.001; ns, not significant. 387 1982;Vekiari et al 2002) and also in other citrus than lemon EOs (Frizzo 2004). However, our results did not agree with the previous studies for some main components of EOs which, in our study, were more concentrated in later collection times.…”
Section: Chemical Composition Of Lemon Eoscontrasting
confidence: 99%
“…c P-value: *P # 0.05; **P # 0.01; ***P # 0.001; ns, not significant. 387 1982;Vekiari et al 2002) and also in other citrus than lemon EOs (Frizzo 2004). However, our results did not agree with the previous studies for some main components of EOs which, in our study, were more concentrated in later collection times.…”
Section: Chemical Composition Of Lemon Eoscontrasting
confidence: 99%
“…7,8 Similarly, in agreement with our previous results, the two remaining samples belonged to the limonene/γ-terpinene chemotype. Is it noticeable that the chemical composition of the cold pressed peel oil of the Montenegrina cultivar from Brazil, recently reported by Frizzo et al, 20 is very close to that reported here (limonene/γ-terpinene = 70.3-73.2%/17.2-19.8% in Brazil against 69.4/17.1% in Corsica, Sample 30).…”
Section: Leaf Oilssupporting
confidence: 89%
“…The essential oils may be extracted through different methods whose use depends on the desired yield and quality and the location of the oil glands (Mazen, 2002). Some of these methods are: steam distillation, cold pressing, peel compression, hydrodistillation, and supercritical fluid extraction (Mazen, 2002;Frizzo et al, 2004;Gil and Sáez, 2005;Atti-Santos et al, 2005). After the extraction, the identification of the compounds in the oil is important; chromatography is the most-used alternative (Mondello et al, 2003).…”
mentioning
confidence: 99%